Productivity and profitability of Bilatidhonia intercropped with cucurbit vegetables (Bangladesh Journal of Agricultural Research, 2008)
The experiment was conducted to find out a suitable intercrop combination of Bilatidhonia and winter pumpkin relayed with different summer cucurbits (Bilatidhonia + winter pumpkin)/summer cucurbits) in the hill valley of the Agricultural Research Station (ARS), Raikhali, Rangamati during 2003-04 and 2004-05. The results revealed that all the intercrop combinations gave the highest fresh yield of Bilatidhonia than that of the sole Bilatidhonia with an exception of Bilatidhonia + winter pumpkin followed by ash gourd and summer pumpkin combination. Maximum fresh yield of Bilatidhonia (50.13 t/ha) was recorded from Bilatidhonia + winter pumpkin closely followed by ribbed gourd and bitter gourd (50.00 t/ha) combination which showed 15-15.5% higher than that of sole Bilatidhona. Summer cucurbits relayed with Bilatidhonia after harvesting of winter pumpkin gave reasonable good yield where ribbed gourd produced the highest yield (15.29 t/ha). Winter pumpkin intercropped with Bilatidhonia also produced reasonable good yield ranging from 31.88 to 32.68 t/ha compared to the sole winter pumpkin. The highest Bilatidhonia equivalent (69.02 t/ha) and gross return (Tk. 10,35,35,440/ha) were obtained from (Bilatidhonia + winter pumpkin)/ bitter gourd or ribbed gourd combination. But intercropped Bilatidhonia with winter pumpkin relayed by ribbed gourd gave the highest gross margin (Tk. 859, 566/ha) with maximum benefit-cost ratio (4.90) at hilly area of Raikhali, Rangamati.DOI: http://dx.doi.org/10.3329/bjar.v32i3.536Bangladesh J. Agril. Res. 32(3) : 349-357, September 2007